Legal culture in a turbulent time: law and society in early modern Saxony - Jordan, JFD (2013)
This thesis reconstructs and interprets the evolution of legal culture in the Saxon city of Freiberg in the sixteenth century. It challenges the notion that early modern state institutions were punitive and disciplinary; and instead posits that in Saxony, they were flexible and sought to maintain social harmony. While previous scholarship has favoured a sociological approach, based on the concept of social control, this thesis employs a legal anthropological optic to study the interaction of state institutions and social life holistically. The focus is not just on how state institutions sought to regulate social life, but also on how ordinary people used institutions for their diverse purposes. The goal of this methodological approach, based on Lawrence Friedman’s concept of legal culture, is to assess the relative position and interaction of the people, the judiciary, and the law in early modern Germany. Probing the interactions of the court and the residents of Freiberg reveals that the court was primarily a record-keeper and a mediator. For the former, it logged and transcribed all manner of transactions: peace pacts, loans, and house purchases; and Freibergers readily turned to the court to get a formal record of an obligation. For the latter, the court was rarely a site of punishment, rather it was a place where conflicts were regulated, and bonds forged. At court, Freibergers fostered ties to one another. Neither of these roles, record-keeper or mediator, are ones traditionally ascribed to early modern courts. Only by considering by the culture of a court does either become apparent.